Transformación y Aprendizaje Organizacional (2018)
The learning of employees in a company is the most important thing, since over time globalization generates a constant change in cultural, social and economic aspects directly affecting each of the companies or organizations. Organizational transformation and learning are indispensable in a company since it includes everything necessary to carry out the teaching of new technologies or topics to each of the workers.